2005
DOI: 10.1161/01.atv.0000168414.06853.f0
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Dimethylarginine in Idiopathic Pulmonary Arterial Hypertension

Abstract: Objective-We explored the potential role of the endogenous NO synthase inhibitor asymmetrical dimethylarginine (ADMA) in patients with idiopathic pulmonary arterial hypertension (IPAH). Method and Results-We correlated plasma ADMA levels and cardiovascular indices from right heart catheterization in 57 patients with IPAH. Predictors of survival in patients with IPAH were studied. Furthermore, the effect of systemic ADMA infusion on pulmonary ventricular resistance and stroke volume was investigated in healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
139
1
15

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(168 citation statements)
references
References 41 publications
13
139
1
15
Order By: Relevance
“…In IPAH, plasma levels are significantly higher than in healthy, matched controls [71]. In such patients, plasma ADMA correlates positively with right atrial pressure, and negatively with mixed venous oxygen saturation, stroke volume, cardiac index and survival.…”
Section: Asymmetric Dimethylargininementioning
confidence: 87%
“…In IPAH, plasma levels are significantly higher than in healthy, matched controls [71]. In such patients, plasma ADMA correlates positively with right atrial pressure, and negatively with mixed venous oxygen saturation, stroke volume, cardiac index and survival.…”
Section: Asymmetric Dimethylargininementioning
confidence: 87%
“…In our study, however, patients with CKD stage 5 were excluded. Other studies on mortality and dimethylarginines in nonrenal patients (9) or patients with CKD 1 through 4 (34) failed to quantify SDMA. A recent study by Wanby et al (35), involving 363 patients, reported that there was a significant positive multivariate relationship between SDMA and cardioembolic infarction.…”
Section: Why Did Sdma Not Predict Cardiovascular Events and Mortalitymentioning
confidence: 99%
“…У больных с идиопатической (а не только гипо ксической) легочной артериальной гипертонией уровень ADMA также был существенно выше, чем у здоровых лиц [9]. Недавно J. Leiper et al [10] устано вили исключительно важную роль DDAН в регуля ции тонуса легочных сосудов.…”
Section: Chronic Pulmonary Hypertension and Nitric Oxideunclassified